(untitled) (International Journal of Engineering and Computer Science, 2015)
One of the challenging issues for OFDM is its high Peak to Average Power Ratio (PAPR) which limits its applications in wireless communication systems using multicarrier modulation technique as OFDM, which reduces the efficiency of transmit high power amplifier. In this paper, we introduced companding technique with different value of µ. Later in this paper, simulation results show the PAPR and BER performance and then comparison by changing modulation scheme without any technique and with companding technique are evaluated.